Odpowiedzi

2009-11-15T10:39:54+01:00
√3 + 2 / 2 - √3 = (√3 + 2)(2 + √3) / 4 - 3 = 4√3 + 7

3√5 + 1 / √5 + 3 = (3√5 + 1)*(√5 - 3) / 2 = 15 - 9√5 + √5 - 3 /2 = 6 - 4√5

4 + √8 / 2 - √2 = 1 + √8/4 + √2/2
1 1 1
Najlepsza Odpowiedź!
2009-11-15T10:44:32+01:00
(√3 + 2 ):( 2 - √3)=
=[(√3 + 2 )( 2 +√3)]:[( 2 - √3)( 2 + √3)]=
=(3+4√3+4)(4-3)=(7+4√3)

(3√5 + 1 ):( √5 + 3)=
=[(3√5 + 1 )(√5-3)]:[( √5 + 3)(√5-3)]=
=(15-9√3+√5-3):(5-9)=
=-(12-9√3+√5):4

(4 + √8) :(2 - √2)=
=[(4 + √8)(2+√2)] :[(2 - √2)(2+√2)]=
=[8+4√2+2√8+4]:[4-2]=
=[12+8√2]:2=
=6+4√2